A Proposal for Long-Term Missions of Small Lunar Rovers Using an MLI Curtain System. (2nd July 2019) - Lee, Jang-Joon; Kim, Kyu-Hong
Abstract : This paper proposes a lunar night survival method for small rovers using an MLI (Multilayer Insulation) curtain system for long-term missions. Until recently, it was difficult to install RHU (Radioisotope Heating Units) or other temperature maintenance devices on small lunar rovers to enable lunar night survival, and so such rovers could only perform short two-week missions. Thermal analysis results show that small rovers could survive during lunar nights by moving into a shelter located inside the MLI curtain of the lander without mounting temperature maintenance devices. In order to enhance the feasibility of the MLI curtain system, we also propose ideas of a double-layer MLI and a rover configuration without solar cells.